Census of Governments, 1977: Employment Summary Statistics ([Verlag nicht ermittelbar], 1984)
This data collection contains October 1977 employment and payroll figures by function for state and local governments. Full-time and part-time employment and payrolls are shown for corrections, education, administration, fire protection, health, libraries, police, public welfare, utilities, parks, transit, sewage, and highways. Data are also included for labor-management relations, employee benefits, health, hospital or disability insurance, and life insurance. There are seven files in this data collection. Parts 1-5 provide data for each individual state and local government. Part 6 includes data for county areas (local governmental units within each county). Part 7 contains a United States summary and state summaries for the following types of governments: state and local government total, state government, local government total, local governments in standard metropolitan statistical areas (SMSAs), counties, municipalities, townships, school districts, and special districts.